Sistematización de las composiciones de los músicos empíricos y populares de la parroquia Saraguro, cantón Saraguro, provincia de Loja y su incidencia en el desarrollo del patrimonio cultural. Periodo 2010-2011 - Pacají Ruiz, Gabriela Michelle (2013)
The present research allows an approach to the reality of the musical production of empirical and popular musicians of the parish Saraguro, in order to take action to identify research and promote music products, both as artists and community. So, first it raised the general objective: to carry out the systematization of the compositions belonging to the empirical and popular musicians of the parish Saraguro, and through the use of techniques and instruments for the scientific method, it is defined the universe to investigate, it was 380 people (authorities and inhabitants) and 5 empirical and popular composers, who belong to various groups in the parish and have recorded some of his musical creations, this due to the breadth of the universe to explore and the degree of difficulty involved in access to them, reason which were established ten compositions that morphologically structured piano score within genres corresponding to pasacalle, sanjuanito and chaspishca. These results were presented and socialized in an artistic event-musical, which included the participation of musicians investigated in this study. Regarding the formulation of the hypothesis; its statement refers to the positive influence that involves systematizing, organizing and structuring empirical compositions and popular musicians in the development of local cultural heritage. In conclusion it can be mentioned that the preservation and promotion of the musical heritage of the people Saraguro has been possible thanks to the effort of empirical and popular composers consulted, it was possible that their musical ideas transcend local, national and international. After the above process, as a recommendation, it is suggested to support the initiatives of the empirical and popular musicians of the parish, through training activities and development of their musical production, that help them to improve the artistic quality of their creations.